Financial Literacy Management and Its Influence on Corporate Investment Decision Making in the Era of Digitalization - Khaldun, Faiz Khaldun; Pratiwi Hamzah; Evinalia Yeba; A.Musyarrafah Vetriyani; Sifera Patricia Maithy (Jurnal Informasi dan Teknologi, 2024)
This research analyzes financial literacy management and its influence on investment decision-making in the era of digitalization, with a case study on OVO company. Using a qualitative approach, the study explores how effective financial literacy, supported by digital technology, can enhance the efficiency, accuracy, and quality of investment decisions. In-depth interviews with key informants at OVO revealed that strong financial literacy, combined with the adoption of technologies such as big data analytics and machine learning, plays a crucial role in identifying profitable investment opportunities and managing risks. Additionally, ongoing training and skills development in financial technology are essential in addressing challenges posed by technological changes and regulations. The findings indicate that integrating financial literacy and digital technology not only improves operational performance and transparency but also builds stakeholder trust. Challenges identified include cybersecurity risks, adaptation to new technologies, and complex data management. Recommendations include enhancing security strategies, providing continuous training, and developing integrated data management systems. This research provides valuable insights for other companies in managing financial literacy and investment decision-making in the digital era.